Monitoreo Pedagógico y Desempeño Docente - Ojeda Pandia, Elisban Nelson (Instituto de Investigación y Capacitación Profesional del Pacífico - IDICAP PACÍFICO, 2022)
Peru faces great problems in the educational level. The first problem lies in the lack of quality and equity. We are a country that is too inequitable in terms of the quality of learning, since in the last Student Census Evaluation test (ECE) 2014, applied by the Ministry of Education, the difference between the results of the best qualified region (Moquegua) and the worst rated (Loreto) was abysmal. Second-grade children from Moquegua schools obtained results three times better than those from Loreto in both mathematics and reading comprehension, due to the poor quality of work carried out by teachers. The second problem is the enormous gap that exists between what the higher education system proposes and what the current market needs. The careers in which young people are being trained are often far from the needs of the production system.